How to Start a Conversation and Make Friends - Gabor, Don (London Sudha Publications PVT. LTD., 1994)
Shows how to strike up a conversation with anyone in almost any situation, and provides tips on overcoming shyness, making new friends, and become more confident and successful
Keywords: Conversation -- Friendship